Social determinants of health in the Human Services: a conceptual model and road map for action. Issue 2 (4th May 2019) - Spector, Anya Y.
ABSTRACT: The Social Determinants of Health Framework is well known as a reliable way to understand and predict poor health outcomes and health inequities among individuals who are disproportionately impacted by poverty, discrimination, residential segregation, and other social problems. Since becoming recognized by the public health profession as key to addressing the root causes of poor health among these individuals, integration of social determinants of health (SDOH) interventions in the health-care industry has become a national and global priority. This essay offers a theoretical and practical explanation of the integration of the SDOH in the Human Services by proposing key recommendations and strategies for Human Services Organizations (HSOs) and providers to implement new practices, policies, and research methods that may ameliorate the conditions that create inequities in health.